An unusual cause of recurrent pancreatitis: A gastric duplication cyst with an accessory pancreatic lobe - Türkvatan, Aysel; Erden, Ayşe; Türkoğlu, Mehmet Akif; Bostancı, Erdal Birol; Dişibeyaz, Selçuk; Parlak, Erkan (Turkish Journal of Gastroenterology, 2014)
Abstract Congenital anomalies of pancreas and its ductal drainage are uncommon but in general surgically correctable causes of recurrent pancreatitis. A gastric duplication cyst communicated with an accessory pancreatic lobe is an extremely rare cause of recurrent pancreatitis, but an early and accurate diagnosis of this anomaly is important because suitable surgical treatment may lead to a satisfactory outcome. Herein, we presented multidetector computed tomography and magnetic resonance imaging findings of a gastric duplication cyst communicating with an accessory pancreatic lobe via an aberrant duct in a 29-year-old woman with recurrent acute pancreatitis and also reviewed other similar cases reported in the literature.